Case report: Bilateral pleural effusion secondary to late migration of a tunneled central venous catheter in a patient affected by high risk neuroblastoma - D'Angelo, Tommaso Domenico; Persano, Giorgio; Crocoli, Alessandro; Martucci, Cristina; Parapatt, George Koshy; Natali, Gian Luigi; Inserra, Alessandro (Frontiers in Pediatrics, 2022)
The insertion of long-term central venous catheters is a standard of care for children affected by malignancies, although it can be associated with life-threatening complications. The present paper reports an unusual mechanical complication related to the use of a long term tunneled central venous catheter in a pediatric oncologic patient. An 18 months old child, diagnosed with stage M high-risk retroperitoneal neuroblastoma, underwent ultrasound-guided placement of a 6 Fr bilumen long-term tunneled central venous catheter in the right internal jugular vein prior to the beginning of induction chemotherapy. The correct position of the distal tip of the catheter was confirmed by fluoroscopy. After four months of regular use of the device, the patient experienced neck swelling during high-dose chemotherapy infusion. A chest x-ray showed a dislocated catheter and bilateral pleural effusion. CT scan demonstrated the tip of the catheter rupturing the medial wall of the right jugular vein and entering the mediastinum; furthermore, pneumomediastinum, subcutaneous neck emphysema and bilateral pleural effusion were noticed and a thrombus was evident in the right jugular vein at the insertion in the brachiocephalic vein. The patient was then transferred to the Intensive Care Unit and bilateral thoracostomy tubes were placed urgently (500 mL of clear fluid were evacuated from pleural spaces). The dislocated catheter was removed electively on the following day under fluoroscopy. Despite ultrasound-guided placement and long-term uneventful use of the catheter, life-threatening central venous catheter-related mechanical complications can occur; the current case report emphasizes the importance of careful monitoring of patients with central venous catheters in order to quickly diagnose and treat potentially lethal complications.